The sense of rhythm : a semiotic investigation of a fundamental device - Ceriani, Giulia (Emerald points., 2023)
The importance of rhythm spans time and space, its significance both natural and constructed. As contemporary society challenges us to search for connection, the question of rhythm is profoundly and uniquely capable of managing the exchange and dialogue between deep narrativity and surface figurativeness. A semiotic examination of the regulative efficacy of rhythm is at the centre of The Sense of Rhythm, which frames rhythm as a characteristic of texts and narratives in order to organize and sense meaning. Rhythm is capable of creating and conveying a passionate tone, and of fostering cross-disciplinary and cross-textual convergences. An awareness and recognition of rhythmic structure allows for potential to cross-code between perception and sensation across cultures. This new edition, published for the first time in English, brings semiotician Giulia Ceriani's research to English-speaking students and researchers across disciplines. The Sense of Rhythm serves as a foundation for interdisciplinary research, creative practices, and a unique semiotic approach to the study of rhythm.